Turismo, eventos e etnicidade : Festival Internacional do Folclore Nova Petrópolis - RS - Brasil - Schommer, Luciane Roseli (My University, 2015)
The main theme of this study is the search for a bigger and better understanding of the International Folklore Festival (FIF – Festival Internacional de Folclore), which takes place annually in Nova Petrópolis, Rio Grande do Sul, Brazil; connecting it with tourism, local memories and ethnicity. It tries to discover if FIF, during its forty editions, has contributed to the preservation of the local memory and, at the same time, encouraged the creation of a new social memory from the region. To conduct this research, a qualitative method was chosen, supported in the oral history, since this is the way to interpret the experiences lived by its participants, such as the recognition from the several voices related to the Festival. The data were collected through bibliographic revision, document and field research as interviews and participant observation. This study tried to approximate the theory field to tourism and events, considering the historic background from tourism and FIF in Nova Petrópolis. In the analysis of these themes, dialogues and (inter)relations that indicate the local memory preservation stand out, however the construction of new memories are evident, especially those related to germanness, an imaginary that once created and constructed in the community, would be contributing to an identity construction and a belonging and identity feeling from Nova Petrópolis, related to it.
Este estudo tem como tema central a busca por uma maior e melhor compreensão do Festival Internacional do Folclore (FIF), que se realiza anualmente em Nova Petrópolis, Rio Grande do Sul, Brasil, colocando-o em diálogo com o turismo, as memórias locais e a etnicidade. Busca-se perceber se o FIF, ao longo das suas 40 edições, teria contribuído para a preservação da memória local, ao mesmo tempo em que incentivaria uma nova memória social do lugar. Para a condução da pesquisa, optou-se pelo viés qualitativo com suporte metodológico na história oral, por se entender que este é o caminho para a interpretação das experiências instauradas e vividas pelos participantes, assim como para o reconhecimento das diversas vozes relacionadas com o Festival. Os dados foram colhidos através de revisão bibliográfica, pesquisa documental e de campo, na forma de entrevistas e observação participante. Buscou-se aproximar a área teórica do turismo e dos eventos, considerando o contexto da história do turismo e do FIF em Nova Petrópolis. Na análise destes temas, afloraram diálogos e (inter) relações que indicam a preservação da memória local, mas se evidencia a construção de novas memórias, especialmente aquelas associadas à germanidade, imaginário que, uma vez criado e projetado na comunidade, estaria contribuindo para a construção de uma identidade e um sentimento de pertencimento e identidade de Nova Petrópolis, a ela associados.
Keywords: Festival Internacional de Folclore de Nova Petrópolis; Festas folclóricas - Rio Grande do Sul; Etnicismo; Turismo cultural; International Folklore Festival of Nova Petrópolis; Folk festivals - Rio Grande do Sul (Brazil); Folk festivals - Rio Grande do Sul (Brazil); Ethnicity; Heritage tourism